The contribution of step characteristics to sprint running performance in high-level male and female athletes - Debaere, S.; Jonkers, I.; Delecluse, C. (The Journal of Strength and Conditioning Research, 2013)
We investigated the interaction between step length and step rate and its effect on sprint performance in male and female sprinters during initial acceleration (IA) (0-10 m), transition phase (TP) (10-30 m), and at maximal speed (MS). Ten high-level male and female sprinters ran 2 all-out 60-m sprints. Force-time characteristics of start action were recorded by means of instrumented starting blocks. Running speed and acceleration were recorded using a laser system (ULS), whereas step length and step rate were measured for each step (Optojump). Step length was normalized for leg length. Explosive strength of the lower limb muscles was quantified using vertical jump performance, showing a 24.6% higher score in men compared with women. During the 3 phases of sprinting, step rate remained constant and did not differ significantly between men (IA: 4.37 ± 0.21 Hz, TP: 4.47 ± 0.25 Hz, MS: 4.43 ± 0.18 Hz) and women (IA: 4.23 ± 0.18 Hz, TP: 4.34 ± 0.18 Hz, MS: 4.28 ± 0.17 Hz). The data analysis indicates that step characteristics interact differently in men and women across phases. Men do not take full advantage of their higher explosive strength to develop step length and speed during IA, because normalized step length differed only slightly (-4.09%) between men (1.70 ± 0.21) and women (1.66 ± 0.13). However, men outscored women clearly in acceleration (+34.5%) during the TP because they were capable of developing higher step lengths (2.04 ± 0.12 m in men vs. 1.85 ± 0.07 m in women), even when normalized for leg length (2.65 ± 0.12 in men vs. 2.47 ± 0.22 in women). At MS, it was concluded that men and women pursue an optimal balance between step rate and step length because a high negative correlation was found in both sexes (r = -0.94 and r = -0.77). Therefore, training approach needs to be customized to gender-related differences in step length-rate interaction.